El santuario de Qoyllur- rit'i (una peregrinación andina). Expresión y germen de organización campesina - Flores Lizana, J. Carlos (1987)
The pilgrimage to the sanctuary of the Lord of Qoyllur-rit'i is, in the southern Andean region of Peru, one of the most important socio-religious manifestations. In its eight days of celebration, it gathers around thirty thousand Quechua and Aymara peasants from the departments of Cuzco, Puno, Madre de Dios, Apurímac, among others. The internal organization of the pilgrimage-festival, like the cultural, symbolic and religious wealth, has led me to study and reflect on it with great interest, for a long time. The tensions and dynamisms that the country is experiencing are clearly expressed in it, especially in its Andean region, at the socioeconomic, religious and ethnic level. It is therefore one more place, where deep Peru manifests itself and seeks its identity, with all the complex and rich that this process has and that in general the whole country lives. The analysis of this true event will be focused on highlighting the aspects of the organization of the pilgrimage-celebration, but seen within the socio-religious and symbolic tensions in which it occurs. But we will not only describe and analyze it, but my aim is to discover the vital and deep nerves that sustain it, in the same way the gestures of protest and demand that it has, with the attempt to rescue them, for union, religious and political organizations that we try to serve. For this reason, the last point will be the most important and the most bound to dialogue and criticism, since in some way they are the conclusions of the research presented in this article.